On the part that NMR should play in mass spectrometry metabolomics in natural products studies - Borges, Ricardo M.; Teixeira, Andrew Magno (Frontiers in Natural Products, 2024)
The field of metabolomics has witnessed remarkable growth in the context of natural products studies, with Mass Spectrometry (MS) being the predominant analytical tool for data acquisition. However, MS has inherent limitations when it comes to the structural elucidation of key metabolites, which can hinder comprehensive compound identification. This review paper discusses the integration of Nuclear Magnetic Resonance (NMR) spectroscopy as a complementary technique to address these limitations. We explore the concept of Quality Control (QC) samples, emphasizing their potential use for in-depth compound annotation and identification. Additionally, we discuss NMR's advantages, limitations, and strategies to enhance sensitivity. We present examples where MS alone falls short in delivering accurate compound identification and introduce various tools for NMR compound identification in complex mixtures and the integration of MS and NMR data. Finally, we delve into the concept of DBsimilarity to broaden the chemical space understanding, aiding in compound annotation and the creation of compound lists for specific sample analyses.